Thinking with affect, embodiment, care and relationality to do and teach critical research differently - Shefer, Tamara (PINS-Psychology in Society, 2022)
Drawing on experiences of research, and teaching research, and other current scholarship within local critical, decolonial and feminist research, I argue the importance of a more nuanced application of reflexive practices in research. Located in the larger project of social justice in higher education and critical feminist psychology, the paper reflects on the continued dominance of extractive and representational practices in the humanities and social scientific research in general. It also explores the limitations of normative critical reflexivity in qualitative research. Qualitative research does not necessarily avoid repeating epistemologically violent practices and outcomes, and claims of reflexivity may obfuscate these. The article shares some thoughts about how we may disrupt normative research practices, through our work in the university with scholars and in our own critical psychological research, to destabilise dominant forms and pedagogies of research. In arguing for the re-invigoration of nuance and vigilance in the multi-layered politics of our research, the paper suggests the centrality of embodiment, affect, care and relationality in efforts to disrupt problematic practices and outcomes of normative research. The paper also explores two possible avenues of innovative methodological work in research and in teaching research which works through alternative modalities foregrounding such embodiment, affect, care and relationality. These include the participatory-active research of photo-voice, and transversal collaborations across the knowledges of scholarship, art and activism to co-construct knowledge and “think with” our research and pedagogical programmes.